ANKLE-HIGH TROUSERS AND STIGMATIZATION: A VICTIMOLOGICAL ANALYSIS OF SYMBOLIC DISCRIMINATION IN MODERN CORPORATIONS - Andi Zulfa Majida; Sunaryo Sunaryo (Adisam Publisher, 2025)
Symbolic discrimination in the workplace represents a form of structural violence often overlooked by criminal law and human rights protection mechanisms. One manifestation of this discrimination is the stigmatization of religious expressions manifested through attire, such as the wearing of ankle-high trousers (cingkrang), frequently associated with particular religious groups. Although such expressions do not violate legal norms or professional ethics, they often become the basis for social exclusion, professional marginalization, and ideological labeling that harm individuals within professional settings. This article analyzes the forms of victimization experienced by individuals expressing religious identities through a victimological lens and within the framework of symbolic discrimination. Utilizing a normative-juridical approach, this study examines constitutional guarantees of religious freedom, protections against discriminatory treatment as outlined in Law No. 39 of 1999 on Human Rights, and international instruments such as ILO Convention No. 111. Additionally, it explores the relevance of provisions within the Indonesian Penal Code (KUHP) that could potentially be used to protect victims of symbolic discrimination. The findings reveal that discrimination against religious symbols creates unjust power relations and causes psychosocial harm to victims—harm that is often beyond the reach of conventional criminal law. Thus, this study advocates for an expansion of victimological perspectives within criminal law policies to address non-physical yet systemically harmful acts against individual dignity in professional settings.